Leventhal, Dennis A., Sino-Judaic Studies: Whence and Whither, An Essay and Bibliography and The Kadoorie Memoir, Hong Kong, Hong Kong Jewish Chronicle, 1985. Monographs of the Jewish Historical Society of Hong Kong, vol. 1. - Botton Beja, Flora (El Colegio de México, 1989)
Chan Sui-Jeung, The Jews in Kaifeng. Reflections on Sino-Judaic History, Hong Kong, Hong Kong Jewish Chronicle, 1986. Monographs of the Jewish Historical Society of Hong Kong, vol. 2.